Nutritional and anti-nutrient composition of Karaya gum tree (Sterculia setigera) seed: a potential fish feed ingredient - Kehinde Moruff Adelakun; Moshood Keke Mustapha; Damilare Ibukun Ogundiwin; Ambrose A Ihidero (Journal of Fisheries, 2014)
The nutritional and anti-nutritive composition of Karaya gum tree (Sterculia setigera) seed collected from Federal College of Wildlife Management estate, New Bussa, Nigeria was evaluated from October to December, 2013 with the aim of providing data that will guide the effective utilization and inclusion of this under exploited tropical plant seed in fish feed formulation. The seeds were washed, dried, grounded and analyzed for the proximate composition, vitamin and mineral contents as well as the anti-nutritive factors using standard procedures. The result showed that the mean values for the proximate composition were: moisture 5.20%, ash 3.95%, fat 26.03%, fiber 6.15%, protein 13.39% and carbohydrate 45.27%. The plant also contained vitamins and relatively adequate essential mineral elements of nutritional importance of macro elements such as calcium, potassium, sodium, magnesium and micro elements of iron, manganese, zinc and copper. Some anti-nutritional factor such as; alkaloids, phytate, cardiac glycosides, flavonoids, steroids and trace of oxalate were also found in the plant, but their composition will pose no serious  nutritional problem if well processed before its inclusion in fish diet and could therefore be a cheap source of raw materials for the fortification applications in various fish feed formulations.